Drawing as Itself. (Osaka : The National Museum of Art, 1989)
Borofsky, Jonathan ; Darboven, Hanne ; Hollein, Hans ; Ikemura, Leiko ; Kiefer, Anselm ; Knoebel, Imi ; Lewitt, Sol ; Lichtenstein, Roy ; Marden, Brice ; Pichler, Walter ; Polke, Sigmar ; Rainer, Arnulf ; Richter, Gerhard ; Serra, Richard ; Stella, Frank ; Twombly, Cy ; Isozaki, Arata ; Usami, Keiji ; Endo, Toshikatsu ; Kashihara, Etsutomu ; Kano, Mitsuo ; Kawamata, Tadashi ; Kikuhata, Mokuma ; Kobayashi, Masato ; Takamatsu, Shin ; Takamatsu, Jiro ; Tatsuno, Toeko ; Nakamura, Kazumi ; Yano, Michiko ; Yamada, Masaaki ; Lee, U-Fan ; Wakabayashi, Isamu
Drawing as Itself, The National Museum of Art, Osaka, October 7 - November 26, 1989
boek